The Digital Budayawan: Transforming World Music Education Through Online Media - Hayward, Sean (Proceeding International Conference on Malay Identity, 2024)
In recent years, the integration of internet technology, particularly platforms like YouTube, has revolutionized the way that we learn about arts and culture. This presentation explores the concept of the "Digital Budayawan," a term coined to describe the modern-day cultural custodians who harness digital tools to preserve, share, and teach music from diverse global traditions. The accessibility of online platforms has democratized music education, enabling individuals from various cultural backgrounds to learn and engage with world musics beyond geographical limitations. YouTube serves as a virtual classroom where learners can access tutorials, performances, and ethnomusicological insights from around the globe, often directly from native practitioners. Blogs and social media extend this educational landscape by providing spaces for dialogue, reflection, and the dissemination of musicological knowledge. This digital shift has empowered both educators and learners, fostering a more inclusive and interconnected global community of music enthusiasts. However, it also raises questions about authority, authenticity, and what it means to be an educational institution. This presentation examines these dynamics, highlighting how the "Digital Budayawan" navigates the balance between preserving cultural integrity and embracing technological innovation in the field of music education.